Behavior of circular concrete-filled double steel tubular slender beam-columns including preload effects. (1st October 2020) - Ahmed, Mizan; Liang, Qing Quan; Patel, Vipulkumar Ishvarbhai; Hadi, Muhammad N.S.
Highlights: A numerical model for circular CFDST slender columns with preloads is developed. The model incorporates concrete confinement and deformations caused by preloads. The preload effects on the behavior of circular CFDST slender columns is studied. The load distributions in circular CFDST columns with preload effects are examined. The model predicts well the behavior of preloaded circular CFDST slender columns. Abstract: The hollow circular steel tubes support the permanent and construction loads of several upper floors during the construction of a high-rise building structure before the concrete is filled into the steel tubes to form circular concrete-filled double steel tubular (CFDST) columns. The preloads acting on the steel tubes may cause a marked reduction in the performance of slender CFDST columns. This paper presents a numerical modeling technique underlying the method of fiber elements for quantifying the behavior of circular slender CFDST beam-columns loaded eccentrically with preloads acting on the hollow steel tubes. The numerical model considers the concrete confinement, second-order effects, initial geometric imperfection, deformations induced by preloads as well as geometric and material nonlinearities. The dynamic nonlinear equilibrium functions are solved using efficient computational solution algorithms developed. The validation of the numerical modeling technique is made by comparing computations with existing results obtained by experiments and finite element analyses. The influences of preloads on the structural behavior of slender CFDST beam-columns with various important parameters are investigated by means of utilizing the developed computer model. It is shown that the numerical modeling method is an efficient computational simulation and design tool for slender CFDST columns including preloads.